Doing Justice to a Wronged Literature: Essays on Arabic Literature and Rhetoric of the 12th-18th Centuries in Honour of Thomas Bauer - Özkan, Hakan; Papoutsakis, Nefeli (Islamic History and Civilization, 2022)
Doing Justice to a Wronged Literature, a Festschrift for the Arabist and Islamicist Thomas Bauer, includes 17 essays by established academics on various themes and aspects of Arabic literature and rhetoric of the Ayyubid, Mamluk and Ottoman periods (12th-18th centuries).